2022
DOI: 10.3389/fcell.2022.866200
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Applications of N-Cadherin Antagonists and Agonists

Abstract: This review focuses on the cell adhesion molecule (CAM), known as neural (N)-cadherin (CDH2). The molecular basis of N-cadherin-mediated intercellular adhesion is discussed, as well as the intracellular signaling pathways regulated by this CAM. N-cadherin antagonists and agonists are then described, and several potential therapeutic applications of these intercellular adhesion modulators are considered. The usefulness of N-cadherin antagonists in treating fibrotic diseases and cancer, as well as manipulating v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 167 publications
(342 reference statements)
0
15
0
Order By: Relevance
“…Primary invasion and metastasis of PDAC is also corelated to increased expression of N-Cad that stimulates migration and thus helps in survival as well as proliferation of PDAC [58]. So, antagonists of N-Cad help in controlling this metastatic cancer by affecting cell survival, adhesion, proliferation and invasion processes, these antagonists are signi cantly studied in animal models [59]. These antagonists of N-Cad could be phytochemicals as previously reported in other studies [60].…”
Section: Resultsmentioning
confidence: 94%
“…Primary invasion and metastasis of PDAC is also corelated to increased expression of N-Cad that stimulates migration and thus helps in survival as well as proliferation of PDAC [58]. So, antagonists of N-Cad help in controlling this metastatic cancer by affecting cell survival, adhesion, proliferation and invasion processes, these antagonists are signi cantly studied in animal models [59]. These antagonists of N-Cad could be phytochemicals as previously reported in other studies [60].…”
Section: Resultsmentioning
confidence: 94%
“…The importance of the study of E-cadherin is due to its influence on the adhesive properties of the cell, it takes an active part in other processes as well, including the cell cycle and proliferation [29]. Some authors confirm the relationship between the decrease in β-catenin expression and the poor prognosis of the tumor and its clinical and morphological parameters [30].…”
Section: с екція хх іmentioning
confidence: 99%
“…At this time, those clinical and morphological signs that were studied in relation to possible predictors of negative results of conservative treatment, need to determine the dynamics in the treatment process and require "trial therapy" [29]. In this sense, it is possible to predict the effectiveness of progestagen therapy even before it begins, based on the absence or extremely low expression of PGR and E-cadherin and high expression of β-catenin [30]. For women in late reproductive and perimenopausal age, surgical treatment will be considered in such cases.…”
Section: с екція хх іmentioning
confidence: 99%
“…N-cadherin antagonist ADH-1 is the synthetic cyclic peptide (also known as CHAVC and Exherin). The biological effects of ADH-1 on tumors have been extensively investigated in various preclinical animal models and clinical trials [ 198 ]. It was found that ADH-1 treatment significantly enhanced the anti-tumor effects of chemotherapy in melanoma [ 199 ].…”
Section: Potential Therapies For Emt In Copdmentioning
confidence: 99%